2023
DOI: 10.1039/d2qo01699k
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments on 1,2-difunctionalization and hydrofunctionalization of unactivated alkenes and alkynes involving C–S bond formation

Abstract: Alkenes and alkynes are feedstock compounds and key units for many natural products, pharmaceuticals, agrochemicals, and organic functional materials. Hydrofunctionalization and 1,2-difunctionalization of alkenes and alkynes are of the most...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
25
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 131 publications
0
25
0
1
Order By: Relevance
“…For better understanding, the review is categorized according to the mode of reactions viz , (i) C−S bond formation via difunctionalization of alkenes and alkynes, (ii) C−S bond formation via C−H functionalization, and (iii) C−S bond formation via radical cyclization. Though the fragmental aspects of the photochemical C−S bond formation strategy are explained in some of the reviews, this review presents some recent advances in visible‐light driven C−S bond formation [10e–i] …”
Section: Introductionmentioning
confidence: 99%
“…For better understanding, the review is categorized according to the mode of reactions viz , (i) C−S bond formation via difunctionalization of alkenes and alkynes, (ii) C−S bond formation via C−H functionalization, and (iii) C−S bond formation via radical cyclization. Though the fragmental aspects of the photochemical C−S bond formation strategy are explained in some of the reviews, this review presents some recent advances in visible‐light driven C−S bond formation [10e–i] …”
Section: Introductionmentioning
confidence: 99%
“…Radical addition, coupling, rearrangement, and cleavage reactions are powerful in the synthesis of diverse molecular structures [ 1 , 2 ]. Difunctionalization reactions initiated with radical addition are attractive for both synthetic efficiency and product diversity considerations [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. We have recently reported radical 1,2-difunctionalization ( Scheme 1 I) [ 13 ] and addition-/cyclization-based difunctionalization reactions ( Scheme 1 II) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our recent studies, 10 we found that thiirenium ion intermediates, formed by the electrophilic activation of terminal alkynes with dimethyl(methylthio)sulfonium trifluoromethanesulfonate (DMTSM), could be intercepted by triflate ( − OTf) immediately in a Markovnikov manner. 11 Pioneering studies showed that the nucleophilicity of the reagent employed in the ring-opening addition to the thiirenium ion would have significant impact on the regioselectivity.…”
Section: Introductionmentioning
confidence: 99%